If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + g = 0 Solving 9 + g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + g = 0 + -9 Combine like terms: 9 + -9 = 0 0 + g = 0 + -9 g = 0 + -9 Combine like terms: 0 + -9 = -9 g = -9 Simplifying g = -9
| 10x-60=5x+40 | | 21x=500 | | 11=-5-3y | | 2x^2+4x+2=90 | | 21x=500 | | .25x-1.2=1.45x+2.6 | | -2(x-1)-10x-12= | | 2-7+1-4= | | -4(1+2v)=v-13 | | 4xy=-9x+3 | | 41+a=-39 | | -4(1+2v)=v+6k | | 3000+12x=21 | | 4-3w=10 | | 44=5a-1 | | x^2+6x-10=30 | | 13x-24y=-18 | | 9x-30=4x-100 | | -4(x+3)-10x= | | -9y+11=24y | | 6(-6x-8)=120 | | 2-3+3-4= | | 12n=42 | | 110+r=20 | | -81+v=19 | | -5(-3k-2)=1+6k | | 0+(-17)= | | -18=4z-10 | | 7.4p-9.29=2.6+5.3 | | -8b=52-20 | | 7y=3-2xy | | 3000+12x=500 |